1967
DOI: 10.1002/bjs.1800541008
|View full text |Cite
|
Sign up to set email alerts
|

The results of a policy of selective surgical treatment of duodenal ulcer

Abstract: quantitatively greater in patients with duodenal ulcer, it seldom exceeds 40 per cent of the maximum secretory capacity of the stomach as judged by histamine stimulation. Some patients with gastric ulcer, however, showed maximal secretion with antral stimulation. The apparent anomaly between the results of the autoinfusion experiments and those with extract stimulation was resolved by studying the secretory responses to commercial gastrin injected intravenously. Dose response curves indicated that patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

1967
1967
1980
1980

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 4 publications
0
7
0
3
Order By: Relevance
“…Observations on the volume and function of the gallbladder after gastric surgery are contradictory. Many reports (1 [3][4][5][6][7][8][9][10][11][12][13][14][15] suggest that the gallbladder volume doubles after vagotomy or gastrectomy and some authors have shown impaired contractility (14). On the other hand Glanville and Duthie (16) and…”
Section: Discussionmentioning
confidence: 99%
“…Observations on the volume and function of the gallbladder after gastric surgery are contradictory. Many reports (1 [3][4][5][6][7][8][9][10][11][12][13][14][15] suggest that the gallbladder volume doubles after vagotomy or gastrectomy and some authors have shown impaired contractility (14). On the other hand Glanville and Duthie (16) and…”
Section: Discussionmentioning
confidence: 99%
“…TVA is a very effective procedure for reducing gastric acid output and is recommended by some surgeons particularly for patients with a high preoperative acid output (Bruce et al, 1959;Small et al, 1967;Kronborg, 1972;Robbs et al, 1973;Kronborg, 1974). However, antrectomy is said by some to be accompanied by a higher operative mortality (Cox et al, 1969;Herrington, 1969;Johnston et al, 1975) and is associated with an increase in symptomatic side effects (Amdrup et al, 1974) and greater long term weight loss (Goligher et al, 1968).…”
mentioning
confidence: 98%
“…The suggestion that the choice of operation for duodenal ulcer should be based on the results of preoperative acid stimulation tests (Small et al, 1967) depends on the assumption that there is an increased risk of recurrent ulcer with increasing levels of stimulated acid secretion (Kronborg, 1972).…”
Section: Discussionmentioning
confidence: 99%